(untitled) (Medico Legal Update, 2020)
Background/Objectives: The message is being used as a mode of intervention leading to preventive health behaviors and can lead to modifications in knowledge, attitudes and behaviors in a large proportion of health behaviors. The purpose of this study is to identify the effective and persuasive message types among positive and negative message types in information on specific health behaviors, to evaluate the effects by systematically classifying and analyzing related studies and to lead evidence-based practices. Method/Statistical Analysis: In this study, meta-analysis was conducted to evaluate the trends and reporting levels of the study in order to evaluate and systematically classify the effects of message types in information on health behavior. Only clinical studies with randomization comparing the effects of positive and negative message framing with respect to health behavior were selected. In addition, a case where the interventions were compared by dividing them into two groups was selected. Improvements/Applications: Among the final selected papers, 7 papers were included in the included studies through methodological quality evaluation. Comparison of the positive and negative message interventions is related to health behaviors related to breast cancer (SMD -0.04 (95% CI -1.57 to 1.50), health behaviors related to vaccination (MMR, HPV)(SMD 0.20 (95% CI -0.69 to 1.08), cancer screening, vaccination, physical activity and all health activities related to Type 2 diabetes screening (SMD -0.21 (95% CI -0.89 to 0.47). All of these were not statistically significant. In order to confirm the change in health behavior according to message framing, a study considering the same target population and outcome indicators is necessary.